2007
DOI: 10.1371/journal.pone.0000472
|View full text |Cite
|
Sign up to set email alerts
|

Short RNA Guides Cleavage by Eukaryotic RNase III

Abstract: In eukaryotes, short RNAs guide a variety of enzymatic activities that range from RNA editing to translation repression. It is hypothesized that pre-existing proteins evolved to bind and use guide RNA during evolution. However, the capacity of modern proteins to adopt new RNA guides has never been demonstrated. Here we show that Rnt1p, the yeast orthologue of the bacterial dsRNA-specific RNase III, can bind short RNA transcripts and use them as guides for sequence-specific cleavage. Target cleavage occurred at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Their RNase III domains may interact with that of KREN1, KREN2, and KREN3 to create a catalytic site that only cleaves mRNA in the mRNA/gRNA duplex. While RNase IIIs typically cleave both strands of an RNA duplex, cleavage of one strand has been reported, and yeast Rnt1p can catalyze guide-directed cleavage of a single strand (6,7,31,48,50). Having two different proteins, i.e., KREPB4 and KREPB5, may expand the repertoire of editing sites that the editing endonucleases can recognize and cleave.…”
Section: Discussionmentioning
confidence: 99%
“…Their RNase III domains may interact with that of KREN1, KREN2, and KREN3 to create a catalytic site that only cleaves mRNA in the mRNA/gRNA duplex. While RNase IIIs typically cleave both strands of an RNA duplex, cleavage of one strand has been reported, and yeast Rnt1p can catalyze guide-directed cleavage of a single strand (6,7,31,48,50). Having two different proteins, i.e., KREPB4 and KREPB5, may expand the repertoire of editing sites that the editing endonucleases can recognize and cleave.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of RNT1 perturbs the cell cycle and growth, increases the telomere length, inhibits ribosome production, impairs cell wall stress response, and induces temperature sensitivity (Catala et al, 2008). While Rnt1p normally cleaves local stem loop structure, it was shown that the enzyme could direct cleavage in trans by binding to small guide RNA in analogy to the mechanism of RNAi, which is absent in S. cerevisiae (Lamontagne and Abou Elela, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Looking at the Giardia Dicer crystal structure, it is tempting to speculate that the two Dicer selected stems (39-overhang and the binding arm strand) stack together and bind to the flat linker surface in between the PAZ and the RNase domains (MacRae et al 2006) leaving the third stem protruding from the nuclease domain in space. A comparable asymmetric cleavage was also reported when the cleavages of yeast RNase III (Rnt1p) and tRNase ZL were directed in trans using guide RNA (Lamontagne and Abou Elela 2007;Nakashima et al 2007). Therefore, it is likely that this phenomenon is not specific to any given cleavage mechanism, but rather that it demonstrates the inherently limited number of three-way junction conformations that could correctly fit for catalysis.…”
Section: Discussionmentioning
confidence: 58%
“…3A,B). The position of these modifications was chosen not to affect RNA duplex formation or the overall substrate structure based on previous study using yeast and bacterial RNase III Lamontagne and Abou Elela 2007;Lavoie and Abou Elela 2008). Surprisingly, all 29-OMe substitutions were tolerated except for that located at the cleavage site (see RG-20 result).…”
Section: Selective Effects Of 29-ome On Dicer Primary Bindingmentioning
confidence: 99%